The Effect of Ecological Human Resources on Pro-Environmental Work Climate: The Moderating Roles of Management Commitment and Employee Awareness in Private Companies in Bali - Ni Luh Kardini; Wayan Gede Supartha; Hj. Sri Langgeng Ratnasari; Zulkifli Sultan (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study examines the effect of Ecological Human Resources (EHR) on pro-environmental work climate and tests the moderating roles of management commitment and employee awareness. The study used a quantitative cross-sectional survey of 60 employees from private companies in Bali that had environmental programs or sustainability-related policies. Data were collected using a five-point Likert questionnaire and analyzed using Partial Least Squares Structural Equation Modeling. The measurement model met the criteria for convergent validity, discriminant validity, and internal consistency. The structural model showed that EHR had a positive and significant effect on pro-environmental work climate. Management commitment did not significantly moderate the relationship. Employee awareness significantly strengthened the relationship. The model explained 81.1% of the variance in pro-environmental work climate. The findings show that ecological HR practices can shape a greener workplace climate when employees understand environmental issues and translate policy into daily work behavior. Keywords: Ecological Human Resources; Green Human Resource Management; Pro-Environmental Work Climate; Employee Awareness; Management Commitment